Thirty-years Assessment of Size-fractionated Particle Mass Concentrations in a Polluted Urban Area and Its Implications for the Regulatory Framework - Casazza, Marco; Gilli, Giorgio; Piano, Angelo; Alessio, Silvia (Journal of Environmental Accounting and Management, 2026)
Among the different atmospheric pollutants, since the late 70s, great attention has been devoted to Particulate Matter (PM). From a 30-year database of size-fractionated PM measurements, we ob- served the positive impact of the gradual introduction of improved air quality regulations. In fact, PM10, PM2.5 and PM1 absolute con- centration levels have been reduced during this period. In particular the mean recorded values are: 63 μg/m3 (PM10), 38 μg/m3 (PM2.5) and 22 μg/m3 (PM1) in year 1980. Recorded mean values were 59 μg/m3 (PM ), 41 μg/m3 (PM ) and 32 μg/m3 (PM ) in year 2000, 10 3 2.5 3 1 3 and finally 45 μg/m (PM10), 34 μg/m (PM2.5) and 29 μg/m (PM1) in year 2011. Nevertheless, major adverse health effects are still recorded. Even if a complete toxicological description of PM im- pact is still in progress and several aspects related to the chemical and mutagenic effects of PM should be investigated in depth, the relative size concentrations are also of paramount importance. In fact, even if the absolute concentrations of the three inhalable PM fractions decreased, relative concentrations of finer fractions have increased in the period 1980-2010. In particular, the relative values of PM2.5 and PM1 are: 61% (PM2.5) and 35% (PM1) in year 1980; 70% (PM2.5) and 54% (PM1) in year 2000; 75% (PM2.5) and 65% (PM1) in year 2011. Results suggest that the introduction of new limitations to sub-micron particles (PM1) emissions is advisable. Possible improvement of air quality management might derive from differentiated local/regional limitations, depending on the charac- teristics of the exposed population and on the local meteorological and geographical characteristics of the sites showing higher aerosol pollution levels.